2023
DOI: 10.1289/ehp11292
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Transfer of Perfluoroalkyl Substances (PFAS) from Maternal Serum to Breast Milk in Women Highly Exposed from Contaminated Drinking Water: A Study in the Ronneby Mother–Child Cohort

Abstract: Background: Infancy perfluoroalkyl substances (PFAS) exposure from breastfeeding is partially determined by the transfer efficiencies (TEs) of PFAS from maternal serum into breast milk. However, to our knowledge there are no studies of such TEs in highly exposed populations. Objectives: We estimated the TEs of PFAS from maternal serum into colostrum and breast milk in a cohort of women with a wide range of PFAS exposures. Methods: The Ronneby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…Few studies have investigated trophic transfer of PFAS, but studies have shown accumulation of PFBA and other PFAS in crickets after consumption of PFAS-impacted alfalfa, 120 and studies have also shown that PFAS, including short-chain homologues, are transferred to breast milk following exposure. 121–123…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated trophic transfer of PFAS, but studies have shown accumulation of PFBA and other PFAS in crickets after consumption of PFAS-impacted alfalfa, 120 and studies have also shown that PFAS, including short-chain homologues, are transferred to breast milk following exposure. 121–123…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have investigated trophic transfer of PFAS, but studies have shown accumulation of PFBA and other PFAS in crickets aer consumption of PFAS-impacted alfalfa, 120 and studies have also shown that PFAS, including short-chain homologues, are transferred to breast milk following exposure. [121][122][123] To elucidate whether PFAS in produce were attributable to uptake or to PFAS applied or transferred to the outside of the plant (e.g. from pesticides or packaging) 124 fresh produce items were washed, dried, extracted and analyzed a second time.…”
Section: Pfas In Food Productsmentioning
confidence: 99%
“…53 The affinity of PFAS to proteins allows them to bind with serum proteins and be delivered to the mammary gland membrane or transported with phospholipids and regulated by fatty acid transport proteins in human milk. 19 The TE BM of legacy PFAS (PFOA, L-PFOS, PFNA, PFDA, L-PFHxS, and PFUdA) in Sweden and the US were determined to be in the range of 1.02%−2.72% (median) and 1%−4% (mean), 19,41 which are similar to the results obtained in this study (median 0.20%−2.14%, except 4:2 FTS and N-MeFOSAA with the highest TE BM values). Precursors or alternatives such as 4:2 FTS, and N-MeFOSAA have rarely been analyzed in human blood or human milk in previous studies.…”
Section: Concentration Correlations and Transfer Efficienciesmentioning
confidence: 99%
“…Four studies conducted in Sweden and Korea reported higher PFOS concentrations in human milk collected 30 days postpartum compared with those in the colostrum, whereas four other studies reported a decreasing trend in PFOS concentrations. 19,20,24,25 Regarding PFHxS and PFNA, studies have reported elevated concentrations of these substances, along with lactation. However, these studies have only focused on traditional PFAS, which have been banned from production and are used in mostly developed countries following the listing of persistent organic pollutants under Annex B (restriction) by the Stockholm Convention since 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation